Genetic diversity and evolutionary insights of Dali tea (Camellia taliensis) in the Lancang River Basin: Implications for tea breeding and resource conservation. - Yanlan Tao; Lichao Huang; Hongyu Chen; Yiju Luo; Rong Tang; Faying Li; Zengquan Lan (PLoS ONE)
Dali tea (Camellia taliensis), serving as a primitive wild species within the section Thea, represents a crucial genetic source for the domestication of Pu-erh tea (C. sinensis var. assamica) due to its strong stress tolerance and unique biochemical composition. It is of key value for the conservation of tea genetic resources and breeding innovation. Utilizing the SLAF-seq (Specific-Locus Amplified Fragment Sequencing) technique, this study systematically analyzed the genetic diversity and evolutionary relationships among five geographic populations (16 C. taliensis and 4 C. sinensis var. assamica accessions) within the Lancang River basin. Results revealed significant genetic differentiation among the C. taliensis populations. Pronounced genetic isolation was observed between the Lincang Daxueshan and Dali Nanjian populations. Localized gene introgression occurred between wild C. taliensis (Nanjian population) and C. sinensis var. assamica.The wild Lincang Daxueshan population formed a monophyletic clade at the base of the phylogenetic tree, exhibiting strong genetic isolation and high differentiation levels (Fst = 0.364) but low genetic diversity. In contrast, the cultivated population (Banna Germplasm Repository) displayed a mixed genetic background, with wild genetic components constituting only 50%-60%. The Lincang Daxueshan wild population showed a low minor allele frequency (MAF = 0.204) and a mild inbreeding coefficient (Fis = 0.09), indicating a potential risk of genetic erosion. Conversely, the Banna Germplasm Repository population exhibited the highest genetic diversity (Shannon Index = 0.318), highlighting the effectiveness of ex situ conservation and its potential as a vital gene donor for tea breeding. This study underscores the unique status of the upper Lancang River basin in Yunnan as a core conservation area for C. taliensis genetic diversity. We propose strategies of "delineating priority zones for in situ conservation" and "facilitating inter-population germplasm exchange," providing a molecular basis for conserving wild tea resources and breeding for stress resistance. Employing high-density SNP markers, we obtained 5,182,931 loci with an average sequencing depth of 19.30x. This enabled quantification of gene flow between wild and cultivated populations (Nm = 0.18) and clarified the contribution of introgressive domestication to the genetic makeup of cultivated tea. These findings provide a theoretical foundation for understanding interspecific interaction mechanisms in tea plant evolution and hold significant implications for promoting regional ecological conservation and biodiversity maintenance.